Differentiation of human pluripotent stem cells to the neuronal dopaminergic fate - Martins, Ana Rita Ferreira (2016)
Dissertação de Mestrado, Ciências Biomédicas, Departamento de Ciências Biomédicas e Medicina, Universidade do Algarve, 2013